Rapid hamstrings/quadriceps strength in ACL-reconstructed elite alpine ski racers - Jordan, M. J.; Aagaard, P.; Herzog, W. (Medicine & Science in Sports & Exercise, 2015)
Purpose: Because of the importance of hamstrings (HAM) and quadriceps (QUAD) strength for anterior cruciate ligament (ACL) injury prevention and the high incidence of ACL injury in ski racing, HAM and QUAD maximal and explosive strength were assessed in ski racers with and without ACL reconstruction (ACL-R).